Fictionville - Azimi, Negar; Farzin, Media; Haerizadeh, Rokni; Kukielski, Tina; Mahdavi, Sohrab; Mofid, Bijan; Mohebbi, Sohrab (London; Koenig Books, 2015)
A play by Bijan Mofid, Interpretation by Sohrab Mahdavi, Interview by Sohrab Mohebbi. Contributions: Negar Azimi, Media Farzin, Tina Kukielski.
English
Keywords: 21st century; N4390-5098 Visual Arts. Exhibitions